(untitled) (TEST Ticontre. Theory Text Translation, 2020)
Orphic descent and discursive battle in Palais de Justice, by José Ángel Valente Beginning in the 1980s (central period of Valente’s poetics), Palais de Justice constitutes a milestone in the author’s corpus, as it shows an orphic experience of descent to the multiple layers of memory from the judgment that the poet was subject to: penetration into the material of evil. The trial ramifies, while it is configured allegorically in a pretension of totality that seeks to freeze life and discourse in the circle of resentment, affecting the word itself. Hence, the poetic text continuously tries to escape through disguise and fragmentation, showing the various layers that make up the real: the self is decomposed into images, spaces, times and plot passages are juxtaposed, the causal links are broken or the objects dissolve. In this way, attempts are made to explode the "legal idea of ??the beyond" in the very conformation of the discourse, based on a guilt that seeks without ceasing the punishment of the culprit. Facing this threatening level, eros opens a new space, linked to nature and matter, in which time can be stopped. The center of the battle is in the discourse, which has the symbols as its thread, which are born in the continuous sprouting of writing. The poet makes an initiatory journey, finding his reintegration through eros . But in order to do so, he has to face judgment again through the word. As a psychompompo the tuna will act (for it is a god), Orfeo torn apart, which begins, as it ascends from the Erebus, its song. Key words: José Ángel Valente-Palais de Justice-Orfeo-allegory-eros-law-expressionism-symbol